2002
DOI: 10.1080/09603120120110022
|View full text |Cite
|
Sign up to set email alerts
|

Health effect of human wastes use in agriculture in El Azzouzia (the wastewater spreading area of Marrakesh city, Morocco)

Abstract: The use of wastewater and excreta in agriculture constitutes an important source of spread Salmonella strains and protozoan infections into the environment. This practice has been used in El Azzouzia (the wastewater-spreading area of Marrakesh city, Morocco) for several years. The available circumstantial evidence gained from epidemiological and microbiological investigations suggests that the use of untreated wastewater causes an excess of protozoan infections among children living in El Azzouzia (72%) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…Exposure to open sewers can be seen as analogous to exposure to untreated wastewater used for irrigation [27] although, in the latter, the associated risk seems to stem from the consumption of the irrigated vegetables rather than from wastewater contact [28]. Children are more likely to have contact with wastewater exposed in the peridomestic environment than in the fields.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to open sewers can be seen as analogous to exposure to untreated wastewater used for irrigation [27] although, in the latter, the associated risk seems to stem from the consumption of the irrigated vegetables rather than from wastewater contact [28]. Children are more likely to have contact with wastewater exposed in the peridomestic environment than in the fields.…”
Section: Discussionmentioning
confidence: 99%
“…Sewage effluents, agricultural run-off and direct deposit of faecal materials from wild animals and birds are the major sources of the bacteria in aquatic environments (Alcaide et al, 1984;Baudart et al, 2000;Johnson et al, 2003;Abulreesh et al, 2005). Salmonella species have been found in almost all types of aquatic environments that receive faecal contamination, that include drinking water (Bhatta et al, 2007), rivers (Pianetti et al, 1998;Polo et al, 1998;Polo et al, 1999;Dionisio et al, 2000;Lemarchand & Lebaron, 2003;Arvanitidou et al, 2005;Haley et al, 2009), lakes (Claudon et al, 1971;Arvanitidou et al, 1995;Sharma & Rajput, 1996), ponds (Shellenbarger et al, 2008), marine waters (Matinez-Urtaza et al, 2004a;Martinez-Urtaza et al, 2004b;Martinez-Urtaza & Liebana, 2005;Harakeh et al, 2006), run-off water (Claudon et al, 1971), treated and untreated wastewater (Ho & Tam, 2000;Melloul et al, 2002;Espigares et al, 2006, Mafu et al, 2009 worldwide. Abulreesh et al (2004) were unable to detect salmonellae in water samples from a village pond that receives direct faecal contamination from waterfowl, nevertheless, they managed to isolate the bacterium from bottom sediments of the same pond.…”
Section: Aquatic Environmentsmentioning
confidence: 99%
“…Salmonellae can grow in sewage sludge and effluents after treatment, particularly at low temperatures (Danielsson, 1977), consequently, the application of treated sludge on agricultural land and/or irrigation with treated wastewater, and the discharge of treated effluents in aquatic environments may constitute potential public health hazard (Hutchinson et al, 2008). Salmonella was detected in 68.75% of vegetable samples in agricultural land irrigated with wastewater in Morocco (Melloul et al, 2001), moreover, high infection rate with salmonellae was noted in children living in an area with sewage water irrigation practices (Melloul and Hassani, 1999;Melloul et al, 2002).…”
Section: Domestic and Agricultural Wastementioning
confidence: 99%
“…The girls tended to play at home or in the street thus limiting their exposure. Several other studies support the fact that boys are more prone to contracting ascariasis and to parasitiasis in general (Ait Melloul et al 2002;Brito et al 2003). According to our previous parasitological analysis on the liquid waste stream it was observed that Ascaris was the most abundant type of helminth in this effluent (Lamghari et al 2004).…”
mentioning
confidence: 91%